Analysis and Impact of Consumer Buying Behavior in Decision Making Process in Selection of Brands (International Journal of Innovative Research in Engineering & Management, 2021)
The field of Consumer Behavior is the study of  individuals, groups, or organizations.This view focuses more  narrowly on the buyer and the immediate antecedents and  consequences of the purchasing process. Consumer behavior  provides an opportunity to marketers to analyze “activities people  undertake when obtaining, consuming, and disposing of products  and services” is provided and detailed. The consumer behavior may  also be defined as “a field of study that focuses on consumer  activities.” Consumption pattern is understood on the basis of the  discussions on “why and how people use products in addition to  why and how they buy.”
Keywords: Consumer; Brands; Buying